(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To evaluate the changes in IPSS scores, QoL scores, and early complications in patients with large benign prostatic hyperplasia (BPH) treated with bipolar transurethral resection of the prostate (B-TURP). Subjects and Methods: A cross-sectional descriptive study involving 50 patients with large benign prostatic hyperplasia who underwent TURP with bipolar electrosurgical resection at Thai Nguyen Central Hospital from January 2020 to October 2024. Results: The mean of age was 75,82 ± 8,72 (50-95).The IPSS scores preoperative and postoperative were 22,42 ± 6,45 and 8,26 ± 2,20. The QoL scores preoperative and postoperative were 4,58 ± 0,61 and 1,86 ± 0,70. The mean of time for operative 67,84 ± 18,64 minutes, the mean of postoperative time 6,54 ± 2,56 days. No surgical complications were observed. Conclusion: Bipolar transurethral resection of the prostate (B-TURP) is a safe and effective method for improving lower urinary tract symptoms in patients with large benign prostatic hyperplasia.